2016
DOI: 10.1186/s40249-016-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of tuberculosis in Zhejiang Province, China, 2009-2012

Abstract: BackgroundTuberculosis (TB) is an infectious disease of major public health concern. The disease has demonstrated large space-time variations. This study aims to explore the space-time dynamics of TB cases in an economically and geographically dynamic province in China with specific references of TB control for policy makers.MethodsData on all reported TB cases from 2009 to 2012 were collected from the TB program at the Zhejiang Provincial Center for Disease Control and Prevention. We employed time series and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
63
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 41 publications
(42 reference statements)
15
63
0
3
Order By: Relevance
“…The geocoding process was applied, as described in previous studies [1315]. Demographic information and the administrative code of Zhaotong were obtained from the Annual Statistical Report and integrated into the study database.…”
Section: Methodsmentioning
confidence: 99%
“…The geocoding process was applied, as described in previous studies [1315]. Demographic information and the administrative code of Zhaotong were obtained from the Annual Statistical Report and integrated into the study database.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies on the spatial and temporal distribution of TB have demonstrated that TB has a highly complex dynamics and is spatially heterogeneous at the provincial, national, and international levels during certain periods of time; however, the variations in small area are always be ignored by using a relatively large scale [3][4][5][6]. In our previous study, the Moran's I spatial autocorrelation analysis method was used to analyze the TB incidence data from 2009 to 2013 in Qinghai and found that the distribution of TB in this province was not random [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the number of TB infections in China was approximately 930 000, which accounted for nearly 10% of all global infections [2]. A total of 147 941 TB cases were reported from 2009 to 2012 in Zhejiang Province alone [4]. …”
Section: Introductionmentioning
confidence: 99%